The Effectiveness of Using Bandicam in Students’ Speaking English During Midst Covid 19 Pandemic - Erlinawaty Erlinawaty; Salamuddin Selian (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2021)
The study aimed to explore the effectiveness of Bandicam in students’ speaking English at SMA Negeri 1 Merbau from the perspective of the students. A five point Linkert questionnaire was used and a dscriptive analytical approach was adopted. Through the pusposive sampling method, the researcher selected a sample consisting from 36 students. Those students were selected from XI IBB. The questionnaire forms were distributed by hand to all of the selected students. All of forms were filled and retrieved. However, 35 forms are considered valid for analysis. SPSS program was used. The researcher found the Bandicam palyed an effective media in students’ speaking English from the students’ perspective. It was found that Bandicam was capable of assessing students’ amount of speaking effectively. It was found that Bandicam enabled instructors to save their effort. It was found that Bandicam hindered from commiting acts of cheating.